2023
DOI: 10.1186/s43045-022-00272-3
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge, attitude, and skills of telemedicine among mental healthcare providers

Abstract: Background Telemedicine plays a vital role in patient-centered healthcare delivery in the diagnosis, management, and development of future treatment plans for chronic diseases. Results This study revealed that attitude toward telemedicine was high among the studied mental healthcare providers, while it was average among the other studied variables (awareness, knowledge, and skills). Psychiatrists had a high percentage in the studied variables (awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 53 However, Fouad et al, 2023 revealed that attitude toward telemedicine was high among the studied mental healthcare providers while average among the other studied variables [awareness, knowledge, and skills]. 46 These findings indicate that effective TM integration may lead to a positive utilization by the healthcare providers in the PHCs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 53 However, Fouad et al, 2023 revealed that attitude toward telemedicine was high among the studied mental healthcare providers while average among the other studied variables [awareness, knowledge, and skills]. 46 These findings indicate that effective TM integration may lead to a positive utilization by the healthcare providers in the PHCs.…”
Section: Discussionmentioning
confidence: 90%
“…This tool was previously examined for its reliability. 46 The Cronbach’s alpha for the five parameters were as follows: (Awareness = 0.784, Knowledge = 0.625, attitude =0.720, and skills = 0.890. The tool has five sections: The first section of the TM-AKAS covers the awareness parameter and has 12 items that assess the participants’ TM awareness.…”
Section: Methodsmentioning
confidence: 99%
“…This might involve computer access to help medical professionals learn more TM compared to health professionals without access to social media, those with social media usage were more likely to be well-versed in telemedicine [ 26 , 28 ]. Access to social media promotes knowledge TM compared to health professionals who were uninformed of telemedicine, those who were aware of it were more likely to have a solid knowledge of it [ 17 , 29 ]. This might be conscious of nearly knowing about TM.…”
Section: Discussionmentioning
confidence: 99%
“…Another five sessions ( 2 , 5 , 7 , 9 , 10 ) had the complementary use of traditional media and digital media. Another five sessions ( 3 , 4 , 6 , 8 , 11 ) used digital media.…”
Section: Methodsmentioning
confidence: 99%
“…New digital technologies including metaverse, Augmented Reality (AR), and Internet of Things (IoT) focusing on artificial intelligence (AI). Telemedicine and online education are all expected to spread, evolve, and continue to be extensively developed with increasing demands throughout the world ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%